A mountain of millipedes XI. The trachystreptoform spirostreptids of the Udzungwa Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae) - Enghoff, Henrik; Ngute, Alain S.K.; Kwezaura, Revocatus L.; Laizzer, Richard L.; Lyatuu, Herman M.; Mhagawale, Waziri; Mnendendo, Hamidu R.; Marshall, Andrew R. (European Journal of Taxonomy, 2024)
The “trachystreptoform” species of Spirostreptidae, i.e., species which would formerly have been ascribed to the tribe Trachystreptini, from the Udzungwa Mountains are (re)described, including one new genus and five new species: Attemsostreptus reflexus Akkari & Enghoff, 2019, A. cataractae Enghoff sp. nov., A. leptoptilos Enghoff sp. nov., A. julostriatus Enghoff sp. nov., Lophostreptus tersus (Cook, 1896) (= L. ptilostreptoides Carl, 1909 syn. nov.), L. magombera Enghoff sp. nov., and Udzungwastreptus marianae Enghoff gen. et sp. nov. The type material of Lophostreptus regularis Attems, 1909 (= L. tersus) is discussed. The discussion includes paragraphs on the classification and the Udzungwa fauna of Spirostreptidae, on grouping of the Udzungwa trachystreptoform species in relation to altitude, and on the possibly recent immigration of A. reflexus and L. tersus into the Udzungwa Mts.